International Competitiveness of the Furniture Industry in the European Union Countries: A Cluster Analysis - Katarzyna LUKIEWSKA (Communications of International Proceedings, 2021)
The aim of the study was to assess the international competitiveness of the furniture industry in the EU member states. The article discusses the interpretation of the concept of competitiveness at this level of economic analysis. A novel model of measuring the international competitiveness of the industry was used, on the basis of which the factor and result dimensions of the industry's competitiveness were analyzed. Partial indicators used for the assessment were aggregated based on Ward's method in the field of agglomerative hierarchical methods. Homogeneous subsets of "similar" countries were created in terms of selected competitive characteristics. The conducted research shows that the most competitive was the Polish furniture industry, which was characterized by its high competitive potential, share in exports, and the ratio of import-export coverage, as well as the furniture industry in Germany and Italy, where high production potential, market share, productivity, and innovativeness were noted.
Keywords: Furniture; Industry; Competitiveness; Ward Method